2010
DOI: 10.1108/17506221011058696
|View full text |Cite
|
Sign up to set email alerts
|

Modified PROMETHEE approach for assessing energy technologies

Abstract: Purpose - The purpose of this paper is to elaborate a multi-criteria methodology for the performance assessment of energy supply technologies, which also takes into account the dynamics of technological change. Design/methodology/approach -The approach chosen is based on the multi-criteria outranking methodology Preference Ranking Organisation METHod for Enrichment Evaluations (PROMETHEE), which is linked to the concept of technology's life cycle by assigning criteria weights depending on the actual developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 89 publications
1
43
0
1
Order By: Relevance
“…In recent years, due to increasing energy demand, the use of renewable energy technologies has grown dramatically, therefore some of the previous studies have investigated the role of these technologies in different perspectives of energy issues with various techniques of MCDM. For example: Luthra, et al [76] identified the barriers for adoption of renewable and sustainable technologies in India by using the analytic hierarchy process (AHP) technique; Streimikiene, et al [77], ranked and selected some sustainable electricity production technologies by integration of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and MOORA plus Full Multiplicative form (MULTIMOORA) techniques; van de Kaa, et al [78] used the fuzzy MCDM method, fuzzy AHP, for choosing the photovoltaic technologies; Shen, et al [79], with concerns of policy and technology, evaluated renewable energy resources exploiting by application of fuzzy AHP; Zhao and Guo [80] applied superiority linguistic ratings, fuzzy grey relation analysis and the entropy weighting method for assessment of the external benefits of renewable energy power in China; Zhao and Guo [81] also integrated fuzzy entropy and TOPSIS for choosing a thermal power equipment supplier; Stein [82] proposed a novel approach for ranking of several renewable and non-renewable technologies related to electricity production; Doukas, et al [83] presented flexible and direct MCDM methods though linguistic variables for ranking of sustainable technological energy; Balezentiene, et al [84] used fuzzy MULTIMOORA for ranking of sustainable energy crops; Oberschmidt, et al [85] elaborated the Preference Ranking Organisation Method for Enrichment Evaluations (PROMETHEE) technique for evaluation of performance in energy supply technologies and applied the AHP technique for electricity generation based on some renewable energy alternatives such as solar photovoltaic, wind energy, biomass and solar thermal in Pakistan; Zangeneh, et al [86] proposed a model for evaluation and ranking of distributed technologies in Iran; Ren, et al [87] employed fuzzy MCDM (FMCDM) for assessment and ranking sustainability of biomass-based hydrogen technologies; and Troldborg, et al [88] proposed a multi criteria analysis for evaluation and ranking of renewable energy technologies in Scotland.…”
Section: Role Of Decision Making Techniques and Approaches In Sustainmentioning
confidence: 99%
“…In recent years, due to increasing energy demand, the use of renewable energy technologies has grown dramatically, therefore some of the previous studies have investigated the role of these technologies in different perspectives of energy issues with various techniques of MCDM. For example: Luthra, et al [76] identified the barriers for adoption of renewable and sustainable technologies in India by using the analytic hierarchy process (AHP) technique; Streimikiene, et al [77], ranked and selected some sustainable electricity production technologies by integration of Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and MOORA plus Full Multiplicative form (MULTIMOORA) techniques; van de Kaa, et al [78] used the fuzzy MCDM method, fuzzy AHP, for choosing the photovoltaic technologies; Shen, et al [79], with concerns of policy and technology, evaluated renewable energy resources exploiting by application of fuzzy AHP; Zhao and Guo [80] applied superiority linguistic ratings, fuzzy grey relation analysis and the entropy weighting method for assessment of the external benefits of renewable energy power in China; Zhao and Guo [81] also integrated fuzzy entropy and TOPSIS for choosing a thermal power equipment supplier; Stein [82] proposed a novel approach for ranking of several renewable and non-renewable technologies related to electricity production; Doukas, et al [83] presented flexible and direct MCDM methods though linguistic variables for ranking of sustainable technological energy; Balezentiene, et al [84] used fuzzy MULTIMOORA for ranking of sustainable energy crops; Oberschmidt, et al [85] elaborated the Preference Ranking Organisation Method for Enrichment Evaluations (PROMETHEE) technique for evaluation of performance in energy supply technologies and applied the AHP technique for electricity generation based on some renewable energy alternatives such as solar photovoltaic, wind energy, biomass and solar thermal in Pakistan; Zangeneh, et al [86] proposed a model for evaluation and ranking of distributed technologies in Iran; Ren, et al [87] employed fuzzy MCDM (FMCDM) for assessment and ranking sustainability of biomass-based hydrogen technologies; and Troldborg, et al [88] proposed a multi criteria analysis for evaluation and ranking of renewable energy technologies in Scotland.…”
Section: Role Of Decision Making Techniques and Approaches In Sustainmentioning
confidence: 99%
“…Oberschmidt et al [36] also applied the PROMETHEE method for technology selection. In this study various alternatives for provision of heat and power in a municipality in Germany were compared.…”
Section: Elimitation Et Choix Tradusant La Realité (Electre -Eliminatmentioning
confidence: 99%
“…The PROMETHEE methods are one of the best known and most popular outranking approaches used in sustainable energy planning [65]. They have a number of features that are not available in other MCA methods such as the AHP, ELECTRE or TOPSIS [66].…”
Section: Proposed Conceptual Frameworkmentioning
confidence: 99%